2019
DOI: 10.4236/ojog.2019.96089
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid versus Placebo for Prevention of Primary Postpartum Haemorrhage among High Risk Women Undergoing Caesarean Section in Abakaliki: A Randomized Controlled Trial

Abstract: Objective: To evaluate the efficacy of tranexamic acid for prevention of postpartum haemorrhage among women undergoing cesarean section who were at high risk of postpartum hemorrhage. Materials and Method: This was a double blind randomized controlled trial conducted at the Alex Ekwueme Federal University Teaching Hospital Abakaliki from January 2016 to December 2017. One hundred and sixty-eight parturients at high risk of postpartum haemorrhage who underwent caesarean section were randomly assigned to receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
4
12
0
Order By: Relevance
“…In the present study mean age was 24.25±4.02 years in TXA group and 24.23±4.14 years in control group (p=0.945, NS). Our study was found to be comparable with the studies reported by Elhamid et al and Ifunanya et al [9,10] .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study mean age was 24.25±4.02 years in TXA group and 24.23±4.14 years in control group (p=0.945, NS). Our study was found to be comparable with the studies reported by Elhamid et al and Ifunanya et al [9,10] .…”
Section: Discussionsupporting
confidence: 93%
“…Previous history of postpartum haemorrhage was observed in 12(2.4%) and 15(3%) women of TXA and control group respectively (p >0.05). These findings found to be comparable with the study reported by Ifunanya et al [10] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This value is similar to the 30.8%, 34.0%, and 30.0% reduction in blood loss reported by Umeora et al [22] in Abakaliki, Maged et al [23] in Cairo, Egypt and Ahmed [24] in Ismaila, Egypt respectively. However, Ifunanya et al [25] from Abakaliki reported a slightly higher reduction in blood loss (45.0%) attributable to preoperative administration of Tranexamic acid. These differences in blood loss may be because of the different time intervals used in assessing the blood loss and the different methods used in the estimation of blood loss in the various studies.…”
Section: Discussionmentioning
confidence: 92%
“…However, it only leads to maternal mortality in about 6.4% of cases while other conditions of obstetric hemorrhage such as the ruptured uterus, placenta praveia, abruption, cervical and vaginal trauma, inverted uterus, and adherent placenta mostly result in maternal death. 8 , 9 Currently, various measures including administration of uterotonics, prostaglandins, and active management of 3 rd stage of labor are used to prevent PPH. According to Cochrane review, through active management of labor the incidence of PPH> 1000 ml has been significantly reduced.…”
Section: Introductionmentioning
confidence: 99%